Oleate restores altered autophagic flux to rescue palmitate lipotoxicity in hypothalamic neurons. (1st November 2022) - He, Wenyuan; Tran, Andy; Chen, Chuck T.; Loganathan, Neruja; Bazinet, Richard P.; Belsham, Denise D.
Abstract: Accumulation of excess lipids in non-adipose tissues, such as the hypothalamus, is termed lipotoxicity and causative of free fatty acid-mediated pathology in metabolic disease. This study aimed to elucidate the molecular mechanisms behind oleate (OA)- and palmitate (PA)-mediated changes in hypothalamic neurons. Using the well-characterized hypothalamic neuronal cell model, mHypoE-46, we assessed gene changes through qRT-PCR, cell death with quantitative imaging, PA metabolism using stable isotope labeling, and cellular mechanisms using pharmacological modulation of lipid metabolism and autophagic flux. Palmitate (PA) disrupts gene expression, including Npy, Grp78, and Il- 6 mRNA in mHypoE-46 hypothalamic neurons. Blocking PA metabolism using triacsin-C prevented the increase of these genes, implying that these changes depend on PA intracellular metabolism. Co-incubation with oleate (OA) is also potently protective and prevents cell death induced by increasing concentrations of PA. However, OA does not decrease U- 13 C-PA incorporation into diacylglycerol and phospholipids. Remarkably, OA can reverse PA toxicity even after significant PA metabolism and cellular impairment. OA can restore PA-mediated impairment of autophagy to prevent or reverse the accumulation of PA metabolites through lysosomal degradation, and not through other reported mechanisms. The autophagic flux inhibitor chloroquine (CQ) mimics PA toxicity by upregulating autophagy-related genes, Npy, Grp78, and Il-6, an effect partially reversed by OA. CQ also prevented the OA defense against PA toxicity, whereas the autophagy inducer rapamycin provided some protection. Thus, PA impairment of autophagic flux significantly contributes to its lipotoxicity, and OA-mediated protection requires functional autophagy. Overall, our results suggest that impairment of autophagy contributes to hypothalamic lipotoxicity. Highlights: Palmitate-mediated toxicity arises from the rapid build-up of its metabolites. Oleate reverses palmitate effects even after significant cellular lipotoxicity. Impairing autophagic flux mimics lipotoxicity and is attenuated by oleate. Impairing lysosome fusion prevents oleate-mediated protective effects. Autophagy inducer rapamycin improves palmitate-mediated toxicity.